The influence of nursery substrate and mycorrhiza on growth of transplanted coffee tree seedlings - Siqueira, José Oswaldo; Saggin-Júnior, Orivaldo José; Colozzi-Filho, Arnaldo; de Oliveira, Elizabeth (Pesquisa Agropecuaria Brasileira, 1995)
Non-inoculated (Si) and inoculated coffice tree (Coffea arabica L.) seedlings, raised in soil and in conventional nursery substrate, were transplanted to a soil-vermiculite mix infested and non-infested with arbuscular mycorrhizal fúngi (AMF). Si seedlings raised in soil and transplanted to non-infested soil mix exhibited stunted growth and low tissue P concentration when compared to seedlings transplanted to infested substrate. These effects were reduced in seedlings raised in the conventional nursery substrate and in the pre-colonized ones. However, when Si seedlings were transplanted into AMF-infested soil mix, they became mycorrhizal and benefited from the association, especially seedlings from conventional substrate, which after 120 days of transplant grew as well as the pre-colonized ones. Growth responses were 193% and 131 % for seedlings raised on soil and on conventional nursery substrate, respectively. Such effects did not occur in seedlings pre-colonized by AMF. The importance of soil-mix quality, seedling mycorrhizal status and conditions of the posttransplanting soil on growth and nutrition of coffee plants is discussed.
Keywords: arbuscular mycorrhizac; fungal inoculants; outplants symbiosis; Coffea arabica; nursery